2011
DOI: 10.1111/j.1439-0507.2010.02011.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between the enzymatic activities of Candida albicans pleomorphic forms determined using the api® ZYM test

Abstract: Enzymatic activity profiles for two morphotypes of 37 Candida albicans clinical isolates were compared. Yeast and hyphal forms were grown using yeast extract-peptone-glucose broth or undiluted human serum, respectively. Both morphotypes were documented under scanning electron microscopy. The api(®) ZYM (BioMérieux, France) test was used to evaluate the enzymatic activity profiles for particular pleomorphic forms. None of the examined enzymatic activities showed good agreement (kappa, κ > 0.80) for the two morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Morphological plasticity enables C. albicans colonization and infection of various niches inside the host body (Lu et al 2011). The activity profiles of hydrolytic enzymes differ between yeast and hyphal forms, as various morphotypes play different roles in the particular steps of pathogenesis (Staniszewska et al 2011b). Both the pleomorphism and expression of hyphae-associated genes are regulated by signalizing pathways, such as Rim101 pathway, cAMP-protein kinase A pathway, which include the Efg1p regulator, and a conserved mitogen activated kinase pathway involving Cph1p (Lewis et al 2002;Almeida et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological plasticity enables C. albicans colonization and infection of various niches inside the host body (Lu et al 2011). The activity profiles of hydrolytic enzymes differ between yeast and hyphal forms, as various morphotypes play different roles in the particular steps of pathogenesis (Staniszewska et al 2011b). Both the pleomorphism and expression of hyphae-associated genes are regulated by signalizing pathways, such as Rim101 pathway, cAMP-protein kinase A pathway, which include the Efg1p regulator, and a conserved mitogen activated kinase pathway involving Cph1p (Lewis et al 2002;Almeida et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated (Staniszewska et al, 2011a) that the clinical isolate showed virulence determinants, it produced germ tubes, pseudohyphae, and true hyphae in undiluted human serum. Furthermore, strain 82 showed distinct di erences in activity profiles of hydrolytic enzymes between hyphae and blastoconidia by using the api®ZYM test (Staniszewska et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic and biochemical characterization. e presumptive identification of the clinical strain 82 was conducted using CHROMagar Candida medium (Becton Dickenson, Sparks, MD, USA), as described previously Staniszewska et al (2011b). Colors of the colonies were compared in reference to the C. albicans SC5314 strain.…”
Section: Methodsmentioning
confidence: 99%